IMPROVING STUDENTS’ SPEAKING USING GUESS THE MYSTERY OBJECT GAME IN DESCRIBING THINGS - Rosdamayanti, Novia; Sutapa, Yohannes Gatot; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research was aimed at improving the students? speaking in English, especially in accuracy, fluency, and their encouragement to speak English by using Guess the Mystery Object game technique. The participants were the VII-A grade students of MTs Al-Irsyad Pontianak consists of 36 students. The method of this research was classroom action research (CAR). It was conducted in two cycles. The data in this research was gathered qualitatively by using observation checklist, field notes, and a camera; and was analyzed in a descriptive way. The result of this research showed that the students? accuracy, fluency, and encouragement in speaking English have improved. The implementation of Guess the Mystery Object game encouraged the students to speak English and helped their friends to speak as well. The result of the students? speaking performance was also increased. The students can finally speak English in describing things around school better. In addition, there were 31 students from 36 students who successfully improved their accuracy and fluency of speaking.  Keywords: speaking, accuracy and fluency, guess the mystery object, classroom action research.